Answer:
c would be the correct answer
Step-by-step explanation:
A = b is given to us
Multiply both sides by c to get
a = b
a*c = b*c
The rule to multiply both sides by c is the multiplicative property of equality
Then on the right side, replace c with d. This replacement is possible due to the fact that c = d. This is using the substitution property.
So we go from
a*c = b*c
to this
a*c = b*d
Ans
i cant see the pic
Step-by-step explanation:
Answer:
yuh
Step-by-step explanation:
Answer:
(-4/3), 0.4, 0.8, √2, √11
Step-by-step explanation:
√11=3.316624790355399849114932736670686683927088545589353597058
0.4
(-4/3) = -1.33333333333333333333333333333333333333333333333333333333
0.8
√2=1.414213562373095048801688724209698078569671875376948073176
Thus :
(-4/3)
0.4
0.8
√2
√11